Formation of uniform Fe3O4 hollow spheres organized by ultrathin nanosheets and their excellent lithium storage properties - Ma, Fei-Xiang (2015)
Hierarchical Fe3O4 hollow spheres constructed by nanosheets are obtained from solvothermally synthesized Fe–glycerate hollow spheres. With the unique structural features, these hierarchical Fe3O4 hollow spheres exhibit excellent electrochemical lithium storage performance.